Students’ Perception on The Use of Zoom Application in English Language Learning at SMA Muhammadiyah 3 Palembang - Kumalasari, Diah; Syahri, Indawan; Rositasari, Tri; Badius, Rara (International Journal of Education Research and Development, 2022)
This study entitled Students’ Perceptions on the Use of Zoom Application in English Language Learning at SMA Muhammadiyah 3 Palembang. The main problem of this study was students’ Perception on the Use of Zoom Application in English Language Learning at SMA Muhammadiyah 3 Palembang. The objective of this study was to find out the students’ Perception on the Use of Zoom Application in English Language Learning. The subject of this study were thirty-three students of SMA Muhammadiyah 3 Palembang. This study used aqualitativemethod. The instruments in collecting the data was questionnaire.Based on the students answer from questionnaire, theresearchers concluded that most of students had negative perception about using Zoomapplication in learning English. The students also hasa perceptionthat zoom application was not to effective media to help the students in learning English. Keywords: Students’ Perception, Zoom Application, English Learning.